Pemanfaatan Algoritma Fuzzy Naive Bayes Dalam Pemilihan Bidang Keahlian Mahasiswa Teknik Informatika Universitas Islam Lamongan - Nurul Fuad (Universitas Islam Lamongan, 2019)
One of the factors that can determine the smoothness of students in taking lectures well is the selection of areas of interest in accordance with the abilities of students, meaning that if students determine the choice of majors in accordance with their field of expertise then certainly there will be no difficulty to develop themselves in the lecture process.this study by utilizing two algorithms, namely Fuzzy and Naive Bayes to determine the areas of expertise of students. Informatics Engineering students have the opportunity to choose a field of expertise, namely: the field of network expertise, programming, and design. Not all students will master the area of expertise, so they must choose to accord to their skills, hobbies and favorite subjects, and grades. This research will create a system for classifying the expertise of UNISLA informatics engineering students. The algorithm is implemented, namely Fuzzy to categorize the values or input numbers, while Naïv e Bayes is used for classification